2020
DOI: 10.11591/ijeecs.v18.i1.pp16-23
|View full text |Cite
|
Sign up to set email alerts
|

Simulation modeling for heart attack patient by mapping cholesterol level

Abstract: <p>Cholesterol is a complex structural material made up of four-fused hydrocarbon rings. There is a hydrocarbon tail linked at one end of the structure, while the hydroxyl group linked to each other on the other end. To one end of the structure, a hydrocarbon tail linked and to the other end, a hydroxyl group linked to each other. High cholesterol level is one among the major risk factors of a heart attack. It is feasible to compute and control the cholesterol level of a cardiovascular patient by making … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, Panda et al [15] and George and Gaikwad [16] showed that feature selection [17] improves heart disease diagnosis by using ML models. The CHD diagnosis accuracy is 94.03% when using an embedded bagging feature selection method.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Panda et al [15] and George and Gaikwad [16] showed that feature selection [17] improves heart disease diagnosis by using ML models. The CHD diagnosis accuracy is 94.03% when using an embedded bagging feature selection method.…”
Section: Introductionmentioning
confidence: 99%
“…Iterative feature elimination is model based feature selection method [9], [13]. RFE fits a model and removes feature that does not have effect on predictive outcome of model [11]. In addition, iterative feature elimination removes dependencies and collinearity between features [10].…”
Section: Iterative Feature Eliminationmentioning
confidence: 99%
“…The optimal feature subset selected after removing less informative features using iterative feature elimination consists of feature index (0, 2,4,6,7,9,11,12). The proposed model performed with 98.3% accuracy on heart disease prediction using the optimal feature.…”
Section: Performance Of the Proposed Framework On Optimal Input Featurementioning
confidence: 99%
See 1 more Smart Citation
“…The logistic classifier regression produced optimal outcome accuracy, F1-score and precision of 90.78%, 91.35%, and 90.24% respectively. George and Gaikwad [19] control level of cholesterol in cardiovascular patient through application of system dynamic mathematical models. The model applied recovered the patient faster sporadically.…”
Section: Introductionmentioning
confidence: 99%